PENDAMPINGAN STRATEGI PEMASARAN DIGITAL UNTUK MENINGKATKAN DAYA SAING UMKM BATIK DI DUSUN PIJENAN - Muhammad Sigit Darmawan; Aulia Rahma Kusumaningtyas; Naufal al-Haq; Nisrina Indy Saqifa; Nafa Elifah Khairunnisa; Dani Darmawan; R. Rully Mahendra; Dimas Alfandi; Fahmi Muharomi Dzikri; Adi Putra; Nadiva Freya Danella; Gunawan Budi Susilo (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2025)
Abstract - Digital marketing strategies are crucial factors in improving the competitiveness of MSMEs in the era of globalization. Dusun Pijenan, a batik producer in Bantul Regency, faces challenges in marketing its products. Reliance on conventional marketing methods has limited the market reach of batik MSMEs in Dusun Pijenan. Currently, 80% of batik MSME sales in Dusun Pijenan rely on resellers, while only 20% come from direct buyers. This situation results in lower selling prices to resellers, thereby limiting business revenue. Therefore, a digital marketing training and mentoring program has been designed to assist batik MSMEs in Dusun Pijenan in optimizing digital technology to enhance market potential and competitiveness. This mentoring activity uses the Participatory Action Research (PAR) method, which directly involves MSME actors in the planning and implementation of digital marketing strategies. Several factors, such as limited technological knowledge, difficulties in managing digital marketing accounts, and a lack of personnel to manage digital platforms, pose challenges that need to be addressed during the mentoring process. The results of the activity showed a significant increase in visibility and customer interaction through the creation of digital marketing platforms, such as Instagram and WhatsApp Business. Additionally, the growth in online visitors from the creation of digital platforms was successfully implemented by the seven batik MSMEs in Dusun Pijenan. This mentoring program demonstrates that digital marketing can enhance the market potential and competitiveness of MSMEs in a sustainable manner.